Atogepant for migraine prevention: a meta-analysis of safety and efficacy in adults - Raja, Adarsh; Asim, Rabia; Shuja, Muhammad Hamza; Raja, Sandesh; Muhammad, Tazheen Saleh; Bajaj, Simran; Ansari, Abdul Hadi; Ali, Hamza; Magsi, Iffat Ambreen; Faridi, Muhammad Hammad; Sheikh, Hamza Ali Hasnain; Imran, Muhammad Junaid; et al. (Frontiers in Neurology, 2024)
Background Migraine is a neurological condition marked by frequent headaches, which tends to be accompanied by nausea and vomiting in severe instances. Injectable therapies for migraine, such as monoclonal antibodies that target calcitonin gene-related peptide (CGRP), have proven to be effective and safe. While various oral drugs are available, none have been developed for migraines. Patients prefer oral therapies because they are easier to use, making atogepant, an orally accessible small-molecule CGRP receptor antagonist, a possible alternative. Objectives This systematic review and meta-analysis compared the safety and effectiveness of atogepant with placebo in treating migraine. Methods Adhering to the PRISMA guidelines, we meticulously gathered randomized controlled trials (RCTs) from databases including the Cochrane Library, PubMed, Science Direct, and ClinicalTrials.gov. Studies comparing atogepant with placebo and reporting monthly migraine days (MMDs) as the primary outcome along with secondary outcomes such as monthly headache days and acute medication use days were included. Two independent reviewers conducted the data extraction and quality assessment. Statistical analyses were carried out using RevMan, utilizing risk ratios for dichotomous outcomes and mean differences for continuous outcomes, and a random-effects model. Results Our primary outcome was the change in MMDs over 12 weeks, which showed a significant reduction with atogepant at dosages of 10, 30, and 60 mg. Secondary outcomes, such as monthly headache days, proportion of patients achieving a ≥ 50% reduction in MMDs, acute medication use days, and patient-reported outcomes, consistently showed that atogepant outperformed placebo, highlighting its effectiveness in reducing the migraine burden. Conclusion Higher doses of atogepant are more effective in lowering migraine and headache-related days and increasing quality of life metrics. However, this is accompanied by an increased incidence of adverse events, suggesting the need for careful dose optimization to balance the benefits and risks. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=563395. Unique Identifier: CRD42024563395.